Search for Randall-Sundrum Gravitons in the Dielectron and Diphoton Final States with 5.4 fb(-1) of Data from p(p)over-bar Collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Strauss, M.; et al. (Amer Physical Soc, 2010)
Using 5: 4 fb(-1) of integrated luminosity from p (p) over bar collisions at root s = 1.96 TeV collected by the D0 detector at the Fermilab Tevatron Collider, we search for decays of the lightest Kaluza-Klein mode of the graviton in the Randall-Sundrum model to ee and gamma gamma. We set 95% C. L. lower limits on the mass of the lightest graviton between 560 and 1050 GeV for values of the coupling k/(M) over bar (P1) between 0.01 and 0.1.